Realistic Mathematics Education (RME) Approach Assisted by Kahoot to Enhance Understanding of Mathematical Concepts - Elwi Nuraeni; Vepi Apiati; Elis Nurhayati (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
This study was motivated by the low level of students’ understanding of mathematical concepts, particularly in algebra learning, where students tend to memorize procedures without fully understanding the underlying concepts. Although the Realistic Mathematics Education (RME) approach has been widely implemented to support contextual learning, its application often lacks interactive media that can enhance students’ engagement and participation. The objectives of this study were: (1) to examine whether students who learned through the Kahoot-assisted RME approach achieved better improvement in mathematical conceptual understanding than those who learned through RME without Kahoot, and (2) to determine the magnitude of the effect of Kahoot integration within the RME approach. This study employed a quasi-experimental method with a nonequivalent control group design. The participants were seventh-grade students of SMP Negeri 14 Tasikmalaya, consisting of 26 students in the experimental class and 24 students in the control class. The learning topic focused on algebra. Data were collected through pretest and posttest conceptual understanding tests and analyzed using N-Gain analysis, Independent Sample t-test, and Cohen’s d effect size analysis. The results showed that students who learned through the Kahoot-assisted RME approach demonstrated greater improvement in mathematical conceptual understanding compared to students who learned through RME without Kahoot. The hypothesis test indicated a significance value of 0.009 (< 0.05). In addition, the experimental class achieved a higher average N-Gain score, while the effect size result of 0.696 indicated a medium effect category. The novelty of this study lies in the structured integration of Kahoot as an interactive formative assessment and gamification tool within each stage of the RME learning process on algebra material.